頰粘膜に発生した基底細胞腺腫の1例 - 野口, 博康; 松本, 直行; 浅野, 正岳; 大木, 秀郎; 篠塚, 啓二; 植木, 皓介 (日本口腔外科学会雑誌, 2016)
Basal cell adenoma (BCA) a ccounts for 1.5% to 7.9% of all salivary gland tumors. It frequently occurs in the parotid glands and rarely occurs in minor salivary glands. We report a case of BCA arising in the buccal mucosa. A 50-year-old woman was referred to our department because of a swelling in the left buccal mucosa. Intra-oral examination revealed an elastic-hard mass, approximately 25×20 mm in diameter. Ultrasonography, enhanced computed tomography, and enhanced magnetic resonance imaging showed a well-circumscribed mass. Fluorodeoxyglucose (FDG) -positron emission tomography showed abnormal accumulation of FDG in the buccal lesion. The mass was clinically suspected to be a benign tumor. With the patient under general anesthesia, extirpation of the buccal tumor was performed. Histopathological examination confirmed the diagnosis of BCA. The postoperative period was uneventful. At 18 months, the patient was well, without any complications.